ANALISIS SPEKTRAL TREMBESI (Samanea saman Jacq Merr) MENGGUNAKAN CITRA SPOT 6 DI KAMPUS UNIVERSITAS TADULAKO TONDO PALU - Bantali, Aprianti; Akhbar, Akhbar; Arianingsih, ida; Misrah, Misrah (Jurnal Warta Rimba, 2020)
Earthed are a wide variety of shapes as well as a very diverse color, this can be seen in maps as well as satellite imagery. SPOT 6 has a 60 km Coverage, a better resolution of 1.5 m, blue band addition to get a naturally original color image, allowing it to achieve better efficiently with a large coverage collection of over 3 million km2 per day. Maps can be created based on the way and method of each one of them is by looking at the value of the spectral pixel. The purpose of the study is to know the spectral value of the Trembesi tree (Samanea saman Jacq Merr) using the image of SPOT 6 that is on the Tadulako Tondo Palu UniversityÂ  Campus. The method used in this study is by performing image interpretations to be able to recognize the features/characteristics of objects from trambesy (Samanea saman Jacq Merr) by inflicting SPOT 6 imagery and Arcgis 10.0 software, as well as field surveys to obtain coordinate points). Based on the results achieved by SPOT 6 indicates that the spectral pixel value for the trembetic tree design category (Samanea saman Jacq Merr) has the lowest value of 124 while the highest value of 139, for the trembetic tree pole category (Samanea saman Jacq Merr) has the lowest spectral value of pixel 140 while the highest 159, for the spectral value of spectral pixel. The tree categoryral has the lowest value of 160 is at least value 197, and also the spectral pixel value of the composite yield of band321 that is the minimum (100) and maximum (200), average value (133,16), the and the value of stdv (18,51).Keywords : Interpretation, Spectral Pixel Value